Assessing normality for data with different sample sizes using SAS, Minitab and R - Fitrianto, Anwar; Low, Yen Chin (Asian Research Publishing Network, 2016)
Different statistical packages may produce different results of statistical analysis such as normality test. One of possible sources of the difference is the computational approach. This study tries to explore results of normality tests based on different statistical packages. Empirical data with varied sample sizes were conducted. It was found that SAS, Minitab, and R produced different conclusion in normality test. Meanwhile, sample size also has effect on the test of normality where larger sample size tends to produce different conclusion of normality. But, all the three statistical packages produced similar results of normality test for AD and KS tests.